Accumulation of a Last Deglacial Gravel Layer at Diexi, Eastern Tibetan Plateau and its Possible Seismic Significance - Zhang, Siqi; Jiang, Hanchao; Fan, Jiawei; Xu, Hongyan; Shi, Wei; Guo, Qiaoqiao; Wei, Xiaotong (Frontiers in Earth Science, 2021)
The tectonic and climatic processes controlling conglomerate accumulation in tectonically active regions are the subject of active debate. In this study, the formation mechanism of a gravel layer in the Diexi lacustrine section, eastern Tibetan Plateau, was investigated using dating methods and analysing sedimentary processes. Optically stimulated luminescence (OSL) and accelerator mass spectrometry (AMS) 14C dating show that the gravel layer in the Diexi section accumulated at approximately 16.79 ka BP. The lacustrine layer underlying the gravel layer is severely disturbed, with V-shaped bending at scales of 2-3 m. From the northern to southern sections, the lacustrine layer is continuous and shows no signs of erosion by collapsed debris. Furthermore, the gravel layer is overlain by a lacustrine layer without fining-upwards gradation of particles or sedimentation bedding between the lacustrine and gravel layers. These features indicate that the formation of the Diexi gravel layer was triggered by an earthquake rather than by a debris flow caused by torrential rain. Detailed analysis of satellite images and the sedimentary characteristics of the gravel layer provide evidence for an ancient landslide, which may be related to the gravel layer at Muer village (to the north of the Diexi section). Analysis of the intensity attenuation model in Southwest China implies that the earthquake triggering the landslide was MS > 7.3. Overall, this study has important theoretical and practical significance for understanding the formation mechanism of gravel conglomerate deposits and analysing seismic events through gravel accumulation.